Bolus versus continuous infusion of microbubble contrast agent for liver ultrasound by using an automatic power injector in humans: A pilot study. Issue 3 (24th August 2015) - Quaia, Emilio; Gennari, Antonio Giulio; Angileri, Roberta; Cova, Maria Assunta
ABSTRACT: Purpose: To evaluate the feasibility of using continuous infusion, in comparison with bolus injection, of a sulfur hexafluoride–microbubble contrast agent to prolong the duration of hepatic parenchymal enhancement in humans during sonographic examination. Methods: This pilot study was approved by our institution's ethics committee. Ten patients (5 men and 5 women; mean age ± SD, 65 ± 10 years) each received two injections: a bolus injection (2 ml/s) and then continuous infusion (0.5 ml/min) of the contrast agent by using an automatic injector. Acquired cine clips were transferred to a personal computer, and the video intensity was quantified by dedicated software. Results: From the time of the first microbubble visualization in the scanning plane, maximal enhancement was reached in 6.3 ± 0.94 seconds after bolus injection and in 13.9 ± 1.44 seconds during continuous infusion ( p = 0.002, Wilcoxon's test for paired data). Compared with bolus injection, continuous infusion prolonged the duration of contrast enhancement (4.3 minutes ± 42 seconds versus 7.3 minutes ± 40 seconds; p = 0.002), although no statistically significant difference in maximal enhancement was observed (45 ± 18% for bolus injection and 39 ± 6% for continuous infusion; p = 0.62). Conclusions: Continuous infusion of sulfur hexafluoride–filled microbubbles via an automatic power injector prolongs hepatic contrast enhancement without significantly modifying the maximal enhancement over that at baseline. These data, coming from a pilot study, can be used to design a larger study with adequate statistical power. © 2015 Wiley Periodicals, Inc. J Clin Ultrasound 44 :136–142, 2016